A Study on Constraints Accruing Lodha Women in the Micro Project Developmental Programmes - Bhol, M; Mishra, M; Raj, R K; Mishra, J R (Indian Journal of Extension Education, 2020)
Lodha women are hard worker and family economy mostly depends on them. Lodha Micro Project has formulaÂ ted several programmes for their upliftment in order to bring them into mainstream by leaving their antisocialÂ activities. The study revealed that training for capacity building, exposure visit for confidence development, liasoning for easy credit facilities, close monitoring and guidance to solve the field problems immediately,Â priority towards poverty alleviation, cluster approach, insurance coverage, transparency in programme implementation, developing infrastructures with common agreement along with competency in use, repair and maintenance were the major deficiencies observed which are to be taken into account while formulating action plan by the Lodha Micro Project for sustainable development and empowerment of Lodha women.